Inquiry Training Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Dinamika Rotasi dan Kesetimbangan Benda Tegar - Mutia Rahmadani; Zaturrahmi; Desy Eka Muliani Muliani (ILIN Institute Makassar, 2023)
This research is motivated by several problems, namely the low critical thinking of class XI students of SMAN 14 Padang, teachers have not used varied learning models that can improve students' critical thinking skills. Based on these problems, one of the models that can improve students' critical thinking skills in the material of rotational dynamics and rigid body equilibrium is the Inquiry Training model. The purpose of this study was to determine the effect of the Inquiry Training learning model on students' critical thinking skills on the rotational dynamics and rigid body equilibrium material for class XI SMAN 14 Padang. The method used in this research is experimental and the research design used is quasi-experimental (quasi-experimental), the research design used is posttest only control design. From the data obtained from the analysis of the Mann Whitney Test, the value of 0.00 < 0.05 was obtained. So it can be concluded that H_0 is rejected and H_1 is accepted which reads